Perception, Frequency and Preference in Livestock-Origin Food Consumption During the COVID-19 Pandemic in Indonesia - Sulastri, Endang; A’yun, Annisa’ Qurrotun (2022)
Coronavirus disease 2019 (COVID-19) is a contagious respiratory that produces mild gastrointestinal illness. The infection rate of COVID-19 increases in individuals with low immunity. In an effort to prevent this disease transmission, the Government advocates increasing the immunity level along with consuming healthy and balanced diets. The present study discusses the consumption of livestock-origin foods with high nutrient contents that can bolster immunity and invigorate heart condition. In addition, we have discussed the perception, frequency and preference of Indonesians with respect to the consumption of livestock-origin foodstuff during the COVID-19 pandemic. The consumers’ perception was determined based on the aspects of livestock-origin food, COVID-19 and livestock-origin food consumption. This study was conducted during August to October 2020 on 305 respondents. The data were collected from online questionnaires in a Google Doc™ form. Indonesian consumers demonstrated a positive perception of livestock-origin food consumption in strengthening body immunity to prevent COVID-19 infection; this result was significantly affected by the health status (p≤0.10). Health status also significantly influenced the consumers’ assessment of livestock-origin food consumption (p≤0.10). Furthermore, the income level influenced the livestock-origin food aspect, while gender and level of education influenced the COVID-19 aspect. In terms of purchase frequency, the consumers purchased eggs more frequently during the pandemic, because they were more readily accessible and affordable. Consumers also demonstrated a positive perception with respect to the consumption frequency of meat, milk and eggs (p≤0.05). Consumers’ preference suggested that eggs attained priority during the pandemic period the survey was taken. The income level affected the consumers’ preference for meat, milk and eggs (p≤0.05). Preference for meat was specifically influenced by gender (p≤0.10), for which men showed a strong preference. The consumers’ perception positively influenced the consumption frequency of all livestock-origin food items (meat, eggs and milk). © 2022 Endang Sulastri and Annisa’ Qurrotun A’yun.